Sustained Neutralizing Antibodies 6 Months Following Infection in 376 Japanese COVID-19 Survivors - Goto, Atsushi; Go, Hirofumi; Miyakawa, Kei; Yamaoka, Yutaro; Ohtake, Norihisa; Kubo, Sousuke; Jeremiah, Sundararaj Stanleyraj; Mihara, Takahiro; Senuki, Kotaro; Miyazaki, Tomoyuki; Ikeda, Satoshi; Ogura, Takashi; et al. (Frontiers in Microbiology, 2021)
Objective: There is scarce evidence regarding the long-term persistence of neutralizing antibodies among coronavirus disease 2019 (COVID-19) survivors.This study determined neutralizing antibody titers (NT50) and antibodies against spike protein (SP) or nucleocapsid protein (NP) antigens approximately 6 months after the diagnosis of COVID-19. Methods: COVID-19 survivors in Japan were recruited. Serum samples and data related to patients’ characteristics and COVID-19 history were collected. NT50 and titers of antibodies against NP and SP antigens were measured at 20-32 weeks after the first positive severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) test results. Factors associated with NT50 were identified using the multivariable linear regression and the correlations among NT50 and titers of immunoglobulin G (IgG) and total immunoglobulins (Igs) against NP and SP were assessed by Spearman’s correlation. Results: Among 376 participants (median [range] days after testing positive for SARS-CoV-2, 180 (147-224); median [range] years of age, 50 (20-78); 188 [50%] male), most tested positive for NT50 (n=367, 98%), SP-IgG (n=344, 91%), SP-total Ig (n=369, 98%), NP-IgG (n=314, 84%), and NP-total Ig (n=365, 97%). Regression analysis indicated that higher BMI, fever, and the requirement of mechanical ventilation or extracorporeal membrane oxygenation were significantly associated with higher NT50. Anti-SP antibodies correlated moderately with NT50 (Spearman’s correlation: 0.63 for SP IgG; 0.57 for SP-total Ig), while the correlation was weak for anti-NP antibodies (0.37 for NP IgG; 0.32 for NP-total Ig). Conclusions: Most COVID-19 survivors had sustained neutralizing antibodies and tested positive for SP-total Ig and NP-total Ig approximately 6 months after infection.